The contribution of self determination and peer conformity to sexual harassment - Weni Puspita Sari; Firman Firman (Universitas Negeri Padang, 2021)
This research is motivated by the rise of cases of sexual harassment that occur among teenagers. Sexual harassment by teenagers occurs in verbal, visual, and physical forms such as: sexual jokes, flirting and touching someone's sensitive area. Factors that influence adolescents to commit sexual harassment are due to peer group involvement and the inability of adolescents to make choices in actions that are reflected in peer conformity and self-determination. The aims of this study is to examine the contribution of self-determination to sexual harassment, to examine the contribution of peer conformity to sexual harassment, and to examine the contribution of self-determination and peer conformity together with sexual harassment. This research uses quantitative method with simple and multiple regression analysis. The study population is all students high school city of Padang who are active in 2020/2021. The number of samples in this study were 273 teenagers who were selected by cluster random sampling technique using the Slovin formula. Methods of data collection using self-determination scale, peer conformity scale, and sexual harassment scale with a Likert Scale model to then be tested for validity and reliability. The research findings show that: (1) there is a significant negative contribution between self-determination with sexual harassment shown by correlation coefficient of R= 0.736 and R Square of 0.542, which means that the contribution of self-determination to sexual harassment is 54.2%. (2) there is a significant positive contribution between peer conformity to sexual harassment shown by correlation coefficient of R = 0.767 and R Square of 0.588, which means that the contribution of peer conformity to sexual harassment is 58.8%. (3) there is a significant contribution between self-determination and peer conformity together to sexual harassment shown by correlation coefficient of R = 0.810 and R Square of 0.665, which means that the contribution of peer conformity to sexual harassment is 68.5%.